Association of hypertension and age-related sensorineural hearing loss among elderly: A cross-sectional study - Havilah Twinkle Reddipogu; Mohammed Jaffer Pinjar; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences, 2022)
Background: Hearing loss (HL) has negative impact on quality of life. The prevalence of HL increases with age. Aims and Objectives: The present study was planned to explore the possible association of hypertension with age-related sensorineural HL (SNHL) in the elderly. Materials and Methods: This was a cross-sectional study done in the ENT Department of Great Eastern Medical School and Hospital, Srikakulam. Consecutive sampling method used. Sample size was considered using the formula – 4pq/l2 and 137 subjects from age group 60–75 years were included in the study. Hypertension was verified through a mercury sphygmomanometer and by a systematized questionnaire about hypertension and the use of medication for blood pressure. The hearing was assessed through threshold audiometric and audiological assessment. The study period: 4 months. All patients from the ENT department in the age group 60–75 years and who gave written informed consent were involved in the study. Participants with a history of ear surgery performed in the past, exposure to loud sounds, recently use of ototoxic drugs, patients with hearing aids, and ear diseases were excluded from the study. Results: Out of 137 subjects 52% had hypertension and 48% had no hypertension. Grade 1 hypertensives suffered from mild HL (7.9%), moderate HL (73%), severe HL (11%), and profound HL (7.9%). In Grade 2, hypertensives suffered from moderate HL (11%), severe HL (33.3%), and profound HL (55.5%). The P-value calculated by the Chi-square method was found to be <0.05 and an odds ratio of more than 1, showing a significant association between hypertension and an increase in HL. Moreover, also a statistically positive correlation of MAP and duration of hypertension with age-related SNHL in both ears. Conclusion: HL in the population under study suggested that hypertension is an accelerating factor of degeneration of the hearing apparatus along with age-related SNHL. Hypertension and ageing were significantly associated with the risk of HL. Patients with hypertension have a greater increase in hearing threshold as compared to those without hypertension.